Give My Heart Ease: Filiality and Responsibility in Clarissa in Light of Levinasian and Confucian Ethics - Xiong, Ying (Archīum Ateneo, 2024)
Much has been said about the elements of plot, allegorical allusions, and the Christian design underlying character tendencies in Samuel Richardson’s Clarissa. That said, few scholars notice the intricate mechanism of filiality and responsibility that constantly functions in Clarissa’s ethical quest. Arguably, there are two categories of filiality in Clarissa, one being Levinasian, which always responds to the absolute singularity of the Other, and the other being Confucian, which demands responsibility to a totality. Judging from her struggle, one surmises that two ethical principles colliding within Clarissa’s mind as she responds to her relations mainly arise from her Levinasian sense of responsibility to the Other, which articulates itself as Clarissa’s parenting of the other characters in the novel, and her Confucian, consanguineous love towards her parents expressed in her spirited defense of her family even when they go against her will or treat her terribly. The alternation of these two ethical impulses—which stresses a strain of moral command that contradicts Clarissa’s consistent practice of ethics, a practice that identifies herself as “[a]nother,” or as a self that cannot fully constitute itself without “pass[ing] into the other”—comes to shape her conflicting filiation. Not only do the two incompatible ethical principles agonize Clarissa to a great extent, but it is also this incompatibility that makes her tragedy inevitable. By rereading Clarissa through the prisms of Confucian and Levinasian ethics, this essay attempts to address the ethical principles underlying Clarissa’s many choices germane to her pursuit of peace of mind, namely, an appropriate human distance and the ideal of humanity. It is demonstrable that Clarissa’s insistence on prioritizing optative ethics over the imperative moral norms testifies to her phronesis, which becomes a source of valor for her to do justice to all others than to secure justice for herself in not-so-friendly situations of distress, injustice, and violence.